2011
DOI: 10.1080/19338244.2010.539638
|View full text |Cite|
|
Sign up to set email alerts
|

Visual Contrast Sensitivity in Children Exposed to Tetrachloroethylene

Abstract: This study examined relationships between indoor air, breath, and blood tetrachloroethylene (perc) levels and visual contrast sensitivity (VCS) among adult and child residents of buildings with or without a colocated dry cleaner using perc. Decreasing trends in proportions of adults or children with maximum VCS scores indicated decreased VCS at a single spatial frequency (12 cycles per degree [cpd]) among children residing in buildings with colocated dry cleaners when indoor air perc level averaged 336 μg/m³; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The interested reader is encouraged to read our complete study report available at: http://www.health.ny.gov/environmental/ investigations/perc/perc_vision_report.pdf. A comprehensive description of recruitment and enrollment procedures has appeared in the scientific literature (McDermott et al, 2005); as has a comprehensive description of the influence of residential perc exposure on children's VCS (Storm et al, 2011). The alteration in VCS was very small, limited to visual images of a specific size, and occurred only in children's worse performing eyes.…”
Section: Dear Sirmentioning
confidence: 99%
“…The interested reader is encouraged to read our complete study report available at: http://www.health.ny.gov/environmental/ investigations/perc/perc_vision_report.pdf. A comprehensive description of recruitment and enrollment procedures has appeared in the scientific literature (McDermott et al, 2005); as has a comprehensive description of the influence of residential perc exposure on children's VCS (Storm et al, 2011). The alteration in VCS was very small, limited to visual images of a specific size, and occurred only in children's worse performing eyes.…”
Section: Dear Sirmentioning
confidence: 99%
“…In the case of the NYSDOH (2010) study, significant effects on children are reported from exposures in the range of 0.1 mg/m 3 (100 µg/m 3 ), which is 680-1700-fold below the threshold suggested from occupational and chamber studies. Storm et al (2011; provide no reasonable rationale why normal, healthy children would have this degree of extreme sensitivity compared with normal, healthy adults.…”
Section: Consistency With Other Literaturementioning
confidence: 99%
“…This would appear to be yet another example of Storm et al (2012) presenting evidence that supports their view and marginalizing that which doesn't. It should also be pointed out that nowhere in their recent letter , published paper (Storm et al, 2011), or unpublished report (NYSDOH, 2010) does NYSDOH provide convincing evidence that the wider literature recognizes VCS as the gold standard and most sensitive neurologic test for solvent-induced effects.…”
Section: Selective Reportingmentioning
confidence: 99%
See 2 more Smart Citations